Endoscopic retrograde cholangiopancreatography in patients with surgically altered anatomy: One single center's experience. Issue 52 (December 2016) - Wang, Fei; Xu, Boming; Li, Quanpeng; Zhang, Xiuhua; Jiang, Guobing; Ge, Xianxiu; Nie, Junjie; Zhang, Xiuyun; Wu, Ping; Ji, Jie; Miao, Lin
Abstract : Abstract: Endoscopic retrograde cholangiopancreatography (ERCP) in patients with surgically altered anatomy is challenging. Results of ERCP in those patients varied. The aim of our study was to evaluate the safety and effectiveness of various endoscopes-assisted ERCP in patients with surgically altered anatomy. Fifty-two patients with Billroth II reconstruction (group A), 20 patients with subtotal or total gastrectomy with Roux-en-Y anastomosis (group B), 25 patients with pancreatoduodenectomy or Roux-en-Y hepaticojejunostomy reconstruction (group C) were included. Gastroscope, duodenoscope, colonoscope, and double-balloon enteroscope were used. The endoscope insertion success rate of groups A, B, C was 96.2% (50/52), 85.0% (17/20), 80% (20/25), respectively. χ 2 test showed that there was no significant difference between the 3 groups ( P = 0.068). The mean insertion time was 36.7, 68.4, and 84.0 minutes, respectively. One-way ANOVA showed that the insertion time of group C was significantly longer than that of groups B and C (both P <0.001). The endoscopic cannulation success rates of groups A, B, C were 90%, 82.4%, and 100%, respectively. χ 2 test showed that there was no significant difference between the 3 groups ( P = 0.144). The mean cannulation time was 19.4, 28.1, and 20.4 minutes, respectively. One-way ANOVA showed that the cannulation time of group B was longer than that of groups A and C ( P <0.001, P = 0.001, respectively). In total, 74 patients with successful biliary cannulation achieved the therapeutic goal; thus, the clinical success rate was 76.3% (74/97). Our study showed that ERCP in patients with surgically altered anatomy was safe and feasible.